Submicrometre sampling of living cells by macrophages - Amy C. Fan; Rukman R. Thota; Nina Serwas; Vivasvan S. Vykunta; Kyle Marchuk; Megan K. Ruhland; Lauren Liu; Grace Johnson; Austin Edwards; Matthew F. Krummel (Nature, 2026)
Abstract An effective immune system must sample and develop healthy self-identity to prevent autoimmunity and to discern pathogenic insults 1–3 . Self-proteins are presented to T cells in the thymus during immune cell development 2,3 and must be presented throughout the body to maintain regulatory T cell populations 4–6 and to provide tonic signals to sustain conventional T cells over time 7–9 . Observations of continuous apoptosis in some organs together with the ingestion of that material by myeloid populations has led to a conventional understanding of ongoing cell death as a major source of self-antigens 10 . Here we used a series of companion imaging and vesicular labelling technologies to reveal an alternative process undertaken by macrophages that results in non-destructive, direct sampling of living cells. This process requires cell–cell contact, does not require caspase activation and occurs via trogocytosis-like stretching of the target cell into the macrophage, which leads to the generation of submicrometre-sized vesicles that contain cytoplasm. Using a high-dimensional flow-based method for labelling vesicles, we demonstrate that live-sampled material is distinctly processed and is poorly subjected to fusion with lysosomes. The material also produces differential effects on the presentation of antigen to CD4 T cells compared with CD8 T cells. Disruption of this trafficking by redirecting antigen to the lysosome significantly reduced the associated macrophage-mediated priming of CD8 T cells. These results demonstrate an important and substantial sampling of living cells by the immune system, with clear consequences for maintaining the border of immunity.